Dinamika Perilaku Sosial Remaja Akibat Kekerasan Verbal: Studi Under-Sosial dan Over-Sosial di Kebagusan Jakarta Selatan - Mutia Nurdiana; Irhamni Rahman (Lembaga Pengembangan Kinerja Dosen, 2025)
Verbal abuse is a form of non-physical violence that is often unrecognized but has a serious impact on adolescents' psychological and social development. This study aims to identify the forms of verbal abuse experienced by adolescents and the dynamics of social behavior that emerge as a result in the Kebagusan area, South Jakarta. The research employs a qualitative approach with a phenomenological method, using data collection techniques such as in-depth interviews, observation, and documentation involving ten adolescents who were victims of verbal abuse. The findings indicate that verbal abuse originates from parents and peers, leading to two main behavioral responses: under social behavior, which includes social withdrawal and anxiety; and over social behavior, which manifests as rebellion and aggressiveness. This study emphasizes the importance of awareness regarding the impact of verbal abuse and the need for social and educational interventions to support adolescents’ recovery and the strengthening of their social capacity.